EXPLORING CANVA-BASED ANIMATION MEDIA ON MATHEMATICAL SELF-EFFICACY AND CREATIVE THINKING SKILLS OF STUDENTS - Yuliyanto, Aan; Ramdani, Rizki; Andriyantono, Andriyantono; Sofiasyari, Irma (Auladuna: Jurnal Pendidikan Dasar Islam, 2024)
Abstract The research aims to determine the increase in creative thinking skills and mathematical self-efficacy in mathematics learning through Canva animation media. A non-equivalent control group with a quasi-experimental design was employed in the study. Tests and attitude scales were used in data collection procedures. Utilizing both inferential and descriptive statistics for data analysis. The research result shows that the improvement of creative thinking skills of those who learn with animated media is significantly better than those who learn with conventional learning. However, there was no difference in the students' self-efficacy in the experimental class compared to the control class, and it even tended to decrease. The mathematical self-efficacy of students learning with Canva animated media decreased significantly more than that of students learning with conventional learning. Thus, Canva animation media can significantly improve students’ creative thinking skills, but it cannot significantly improve their mathematical self-efficacy.